Health Risk Assessment of Heavy metals, Physicochemical properties and Microbes in Groundwater near Igando Dumpsite in Lagos, Nigeria - Yahaya, Tajudeen; Chidi, Okeke; Abdulrahman, Sani; Oladele, Esther; Abdulrakib Abdulrahim; Abdulganiyu, Yunusa; Izuafa, Abdulrazaq (Industrial and Domestic Waste Management, 2024)
The most common and cost-effective waste disposal method is the dumpsite; however, leachate from dumpsites may percolate and compromise groundwater sources. This study evaluated the levels of heavy metals (lead, cadmium, chromium, copper, and arsenic), physicochemical parameters (pH, electrical conductivity, total dissolved solids, hardness, calcium, magnesium, and chloride), and microorganisms in borehole water samples obtained at distances of 50, 100, 200, and 400 meters from the Igando dumpsite in Lagos, Nigeria. The health hazards associated with the heavy metals were also calculated. Physicochemical analysis indicated that the water samples were acidic, with pH values ranging from 4.30±0.01 to 5.21±0.008. They contained levels of calcium (166.73±0.01 - 328.66±0.06 mg/l), magnesium (83.72±0.02 - 119.40±0.17 mg/l), hardness (416.01±0.11 mg/l - 820.00±1.63 mg/l), and chloride (20.07±0.02 - 120.90±0.81 mg/l) that exceeded the limits set by the World Health Organization. Heavy metal analysis showed that, in all locations, lead exceeded the permissible limits, cadmium exceeded the limits except for the 400-m location, and copper, chromium, and arsenic (except for the 50-m location) were within permissible limits. The average daily intake and hazard quotient of the heavy metals were both within recommended limits, but the carcinogenic risks of lead, cadmium, and copper in water collected at a distance of ≤100m exceeded the threshold. Microbiological examinations revealed non-permissible levels of bacteria at all locations, coliforms at the 400-m location, and fungi at the 50-m and 400-m locations. On average, the parameters significantly (p<0.05) increased in concentrations as the proximity to the dumpsite decreased. These findings indicate that borehole water is not suitable for drinking without treatment.